FUNCTIONING, MOBILITY AND COMORBIDITY BURDEN IN ELDERLY POPULATION - Kostadinović, Milena; Nikolić, Dejan; Šantrić Milićević, Milena (Medicinski podmladak, 2018)
Aging is physiological process that includes numerous variables, among them: genetics, chronic diseases, lifestyle factors, and socioeconomic factors that interact with one another and thus affecting the person’s functional and physical dimensions. Mobility difficulties are usually among first signs of functional decline and thus affecting the quality of life in aged population. The fundamental dimension of mobility is walking as complex neuromotor activity that integrates sensory and motor functions. With regards to the individual’s needs, adopted physical activity is recommended, in order to take into consideration differences in physical abilities, meaning that such activity was adjusted and modified to the elderly with disabilities needs. Despite the fact that females have lower rates of certain chronic diseases and mortality, they have more functional limitations and are more physically disabled versus males. Most age-dependent disorders arises from disability for which long-term care costs outweigh health expenditure. Technological and medical development, health promotion and redistribution of health and social care services will be important for modifying ageing processes so that people will be living longer without severe disability. Further, on individual level, exercises, walking, cycling, and plays in free time are highly recommended for persons 60 years and older.